Hydrochemical characteristics of the groundwaters in Prilep’s part of Pelagonia valley – Republic of Macedonia (Rudarsko-geološko-naftni zbornik, 2018)
This paper presents the results of hydrochemical investigations of groundwater from the Prilep part of the Pelagonia valley - Republic of Macedonia. These investigations were carried out by analyzing 12 samples of groundwater, taken from the exploitation wells. Samples are taken once a season, during August 2013. Values of the pH were determined with the field digital pH meter, while cations are determined by inductively coupled plasma-atomic emission spectrometry (ICP – AES). For the determination of the anions are used standard EPA methods (gravimetric - TDS, volumetric - Cl-, spectrophotometric - NO3-, NO2-, NH4+ and turbidimetric - SO42- with the spectrophotometer 6715 UV / VIS, Jenway). Тhe maps with spatial distribution of the hydrochemical components were prepared using the IDW (Inwerse Distance Weighting) method for map generation (Geographic Information System software (GIS) ESRI® ArcGis™ 9.2 and its extension Geostatistical Analyst). Spatial distribution maps were constructed according to the coordinates and sample content of each analyzed sample. Samples were taken from the wells which are divided into 3 groups: wells with free level with depth up to 10 m, wells with free level with depth up to 100 m and artesian wells. The graphical methods, Piper diagram and Chadha’s diagram, were applied in order to determine the hydrochemical properties of the groundwater. The results indicate that the groundwater samples have different hydrochemical properties. Ca 2+ >Na+>Mg2+ for the cations and HCO3- >Cl- >SO42-  for the anions were dominantly dissolved ions in the majority of the water samples. Generally, increased values of Ca2+, Mg2+, Na+, K+, HCO3-, K+ and Cl- occur in the groundwater from deeper artesian wells, as a result of the longer retention time of water in the underground and its interaction with the geological environment. Dominant groundwater in Prilep field, in all three types of wells, are waters from hydrocarbonate class (HCO3¯), calcium group (Ca), the first type of water. Groundwater from the shallow wells show the increasing content of K+, NO3- and PO43-which indicates water pollution from fertilization of the cultivated areas, livestock farms as well as communal wastewater. Although hydrochemical data are obtained on the basis of water samples taken only once, they provide an indicative insight into the hydrochemical composition of the water. To obtain more reliable data, taking groundwater samples from wells should be performed multiple times in different seasons.